1999
DOI: 10.1097/00002030-199907300-00006
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 subtype C syncytium- and non-syncytium-inducing phenotypes and coreceptor usage among Ethiopian patients with AIDS

Abstract: Ethiopian patients with HIV-1 C-subtype AIDS harbour a remarkably low frequency of SI phenotype viruses. Coreceptor usage of these viruses correlates with their biological phenotypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
80
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(94 citation statements)
references
References 32 publications
11
80
3
Order By: Relevance
“…Subtype C envelopes have low V3 charges and a high frequency of V3 glycosylation, which is in support of reports describing a low frequency of SI isolates among subtype C-infected individuals even when the patients had low CD4 ϩ cell counts and had progressed to AIDS (69). In accordance, HIV-1 subtypes D and E demonstrate the highest frequency of V3 de-glycosylation, even at the lower V3 charges, and both these subtypes reportedly have a high frequency of SI viruses among infected individuals (71,72).…”
Section: Figsupporting
confidence: 87%
“…Subtype C envelopes have low V3 charges and a high frequency of V3 glycosylation, which is in support of reports describing a low frequency of SI isolates among subtype C-infected individuals even when the patients had low CD4 ϩ cell counts and had progressed to AIDS (69). In accordance, HIV-1 subtypes D and E demonstrate the highest frequency of V3 de-glycosylation, even at the lower V3 charges, and both these subtypes reportedly have a high frequency of SI viruses among infected individuals (71,72).…”
Section: Figsupporting
confidence: 87%
“…quency of syncytium induction (1). Sequence variability in Env V3 among subtype C viruses is not associated with the presence of basic amino acid substitutions, and this is in contrast to that of subtype B viruses (4,9).…”
mentioning
confidence: 96%
“…HIV-1 subtypes may exhibit phenotypic differences. Subtypes are believed to impact on tropism, with some studies associating increased CXCR4 usage with infections with subtype C (Johnston et al, 2003;Connell et al, 2008), and others finding decreased CXCR4 usage in subtype C infections (Bjorndal et al, 1997;Abebe et al, 1999;Peeters et al, 1999;Esbjornsson et al, 2010). Subtypes may have an important effect on transmission of HIV-1, as the subtype B was associated with homosexual transmission and the subtype C with heterosexual transmission (van Harmelen et al, 1997;van Harmelen et al, 2001), but a heterosexually driven subtype B epidemic has been observed in Trinidad and Tobago (Cleghorn et al, 2000).…”
Section: Introductionmentioning
confidence: 99%